Acute study of dose-dependent effects of (−)-epicatechin on vascular function in healthy male volunteers: A randomized controlled trial. Issue 3 (March 2020) - Alañón, M.E.; Castle, S.M.; Serra, G.; Lévèques, A.; Poquet, L.; Actis-Goretta, L.; Spencer, J.P.E.
Summary: Background & aims: There is convincing clinical evidence to suggest that flavanol-containing foods/beverages are capable of inducing improvements in human vascular function. However, whilst (−)-epicatechin has been tested for efficacy, a full dose-dependency has yet to be established, particularly at doses below 1 mg/kg BW. The current study examined the dose-dependent effects of (−)-epicatechin on human vascular function with concurrent measurement of plasma (−)-epicatechin metabolites and levels of circulating nitrite and nitrate species, NOx . Methods: An acute, double-blind, placebo-controlled, crossover intervention trial was conducted in 20 healthy males with 4 treatment arms: water-based (−)-epicatechin (0.1, 0.5 and 1.0 mg/kg BW) and a water only as control. Vascular function was assessed by flow-mediated dilatation (FMD) measured at the brachial artery, laser Doppler imaging with iontophoresis (LDI) at the subcutaneous capillaries of the forearm (response to Ach and SNP) and peripheral blood pressure (BP) at baseline, 1, 2, 4 and 6 h post-intervention. Plasma analysis of epicatechin metabolites was conducted by LC-MS and circulating plasma of nitrite and nitrate species were performed using an HPLC-based system (ENO-30). Results: Significant increases in % FMD were found to occur at 1 and 2 h following intake of 1 mg/kg BW, and at 2 h for the 0.5 mg/kg BW intake. There were no significant changes in LDI or BP at any time-points or intake levels. Increases in FMD over the 6 h timeframe were closely paralleled by the appearance of total plasma (−)-epicatechin metabolites. Non-significant changes in circulating NOx was observed. Conclusions: Our data add further evidence that (−)-epicatechin is a causal vasoactive molecule within flavanol-containing foods/beverages. In addition, we show for the first time that intake levels as low as 0.5 mg/kg BW are capable of inducing acute improvements in vascular function (FMD) in healthy volunteers.